Hubungan Pengetahuan dan Sikap Pedagang Terhadap Penggunaan Styrofoam di Kelurahan 3 Ilir - Rahmi Garmini (jurnal kesehatan terapan sains dan teknologi, 2024)
Background Styrofoam is a food container made of plastic whose basic material is polystyrene, a very light, rigid, translucent and cheap plastic but quickly brittle. Knowledge or cognitive domain is a very important domain in shaping a person's actions. Attitude is a reaction or response that is still closed from a person to an object. Objective of this study was to determine the relationship between knowledge and attitudes of traders towards the use of styrofoam. Method this research method uses the Analytical method using the Cross Sectional approach. The population of this study was all food sellers totaling 131 traders using the Slovin formula to 98 traders and using random sampling techniques. Data analysis used univariate analysis and bivariate analysis using chi-square test statistics. The results of the chi-square test analysis showed the value of each variable, including the relationship between knowledge and the use of styrofoam obtained a p-value of 0.042, the relationship between attitudes and the use of styrofoam obtained a p-value of 0.000. The conclusion of this study shows that there is a relationship between the trader's attitude variable and the use of Styrofoam, while the trader's knowledge variable has no relationship to the use of Styrofoam.